A 0.025-mm2 0.8-V 78.5-dB SNDR VCO-Based Sensor Readout Circuit in a Hybrid PLL- $ΔΣ$ M Structure - Zhao, Wenda; Li, Shaolan; Xu, Biying; Yang, Xiangxing; Xiyuan TANG; Shen, Linxiao; Lu, Nanshu; Pan, David Z.; Sun, Nan (IEEE Journal of Solid-State Circuits, 2020)
This article presents a capacitively coupled voltage-controlled oscillator (VCO)-based sensor readout featuring a hybrid phase-locked loop (PLL)-ΔΣ modulator structure. It leverages phase-locking and phase-frequency detector (PFD) array to concurrently perform quantization and dynamic element matching (DEM), much-reducing hardware/power compared with the existing VCO-based readouts' counting scheme. A low-cost in-cell data-weighted averaging (DWA) scheme is presented to enable a highly linear tri-level digital-to-analog converter (DAC). Fabricated in 40-nm CMOS, the prototype readout achieves 78-dB SNDR in 10-kHz bandwidth, consuming 4.68 μW and 0.025-mm2 active area. With 172-dB Schreier figure of merit, its efficiency advances the state-of-the-art VCO-based readouts by 50×.